Rekonstruksi Kota Kerajaan Semarapura, Kabupaten Klungkung, Bali - Paramadhyaksa, I Nyoman Widya; Laksmi, Ni Ketut Puji Astiti; Karma, I Made Prarabda (Jurnal Arsitektur Universitas Udayana, 2025)
Semarapura, known today as the capital of Klungkung Regency in Bali Province, was the capital of a major kingdom in Bali in the past. In the center of the city there were also various main buildings of the city, such as the castle building, Kerthagosa, Taman Gili, market, and city square. Many of the main buildings of the royal city have been destroyed and transformed, so that the image of the past royal city center only leaves a few buildings. The downtown area of Semarapura Kingdom was mostly destroyed by the Dutch attack that triggered the Puputan Klungkung War in 1908. This research was carried out with a focus on conducting a reconstructive study of the form of the main buildings of the city during the era of Semarapura Kingdom. Data collection was conducted through literature study, interviews, and observations to the downtown area of Semarapura Kingdom. The data and information obtained were then converted into a reconstructive form of buildings in the city center area. This brief paper describes the problems in the process of transferring the verbal data and graphic information collected into a description of the final reconstruction form of various buildings in the downtown area of the kingdom. Keywords: reconstruction, Semarapura Kingdom, city center, royal city